2022
DOI: 10.5826/dpc.1204a179
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast in psoriasis patients with serious comorbidities: a case series and systematic review of literature

Abstract: Introduction: Patients with serious comorbidities are traditionally excluded from clinical trials. Apremilast is not contraindicated in active infections, malignancy and serious hepatic or renal impairment, but real-life data is needed to support this recommendation. Objectives: The aim of this paper is to present our personal as well as literature-sourced real-world evidenced on apremilast use in psoriasis patients with serious baseline comorbidities. Methods: A case-series and systematic literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Bernardini et al observed 28 patients with cancers treated with apremilast for 104 weeks, showing efcacy on both PASI and BSA and without reporting adverse efects [22]. Tsentemeidou et al in a systematic review reported 37 patients with both solid and blood malignancies treated with apremilast with high efcacy and mild side efects [23]. Te same results were reported in a recent French real-world multicenter study [24].…”
Section: Discussionmentioning
confidence: 56%
“…Bernardini et al observed 28 patients with cancers treated with apremilast for 104 weeks, showing efcacy on both PASI and BSA and without reporting adverse efects [22]. Tsentemeidou et al in a systematic review reported 37 patients with both solid and blood malignancies treated with apremilast with high efcacy and mild side efects [23]. Te same results were reported in a recent French real-world multicenter study [24].…”
Section: Discussionmentioning
confidence: 56%
“…It is labeled for moderate-to-severe forms of psoriasis, psoriasic arthritis, and behçet syndrome. Apremilast is indicated in patients who have severe comorbidities like cancer and important infectious diseases [ 45 ]. Different studies remark on its efficacy as an off-label treatment in other dermatologic disorders like atopic dermatitis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to its broad cellular targets and relative tolerability, apremilast has been investigated for its efficacy in chronic inflammatory diseases, including AD and different psoriasis variants ( 15 ). In a recent report documenting the real-life utilization of apremilast in patients diagnosed with both psoriasis and cancer, apremilast demonstrated an improvement in quality of life, while maintaining a favorable safety profile ( 16 , 17 ). Our cases demonstrated the effectiveness of apremilast in achieving remission and maintaining stability without recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral blood mononuclear cells, PDE-4 inhibition reduces the production of pro-inflammatory cytokines, including tumor necrosis factor α, IL-12/23, IL-12, and IL-2, while upregulating the anti-inflammatory cytokine IL-10. Due to its broad cellular targets and relative tolerability, apremilast has been investigated for its efficacy in chronic inflammatory diseases, including AD and different psoriasis variants (15). In a recent report documenting the reallife utilization of apremilast in patients diagnosed with both psoriasis and cancer, apremilast demonstrated an improvement in quality of life, while maintaining a favorable safety profile (16,17).…”
Section: Discussionmentioning
confidence: 99%